2020
DOI: 10.2176/nmc.ra.2020-0091
|View full text |Cite
|
Sign up to set email alerts
|

Genome Engineering Evolves Brain Tumor Modeling

Abstract: Genome engineering using programmable nucleases such as transcription activator-like effector nuclease (TALEN), and clustered regularly interspaced short palindromic repeat-associated protein nine facilitated the introduction of genetic alterations at specific genomic sites in various cell types. These tools have been applied to cancer modeling to understand the pathogenic effects of the growing catalog of mutations found in human cancers. Pertaining to brain tumors, neural progenitor cells derived from human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Genome engineering using CRISPR/Cas9 contributed to the flexibility of tumor modeling with the feasible introduction of bona fide genetic alterations observed in patient tumors [108] . Single-cell RNA-sequencing of adult glioblastoma models derived from human induced pluripotent stem cells (iPSCs) demonstrated that these models recapitulate inter- and intra-tumor heterogeneity observed in glioblastoma patient samples [109] .…”
Section: Modeling Pediatric Gliomasmentioning
confidence: 99%
“…Genome engineering using CRISPR/Cas9 contributed to the flexibility of tumor modeling with the feasible introduction of bona fide genetic alterations observed in patient tumors [108] . Single-cell RNA-sequencing of adult glioblastoma models derived from human induced pluripotent stem cells (iPSCs) demonstrated that these models recapitulate inter- and intra-tumor heterogeneity observed in glioblastoma patient samples [109] .…”
Section: Modeling Pediatric Gliomasmentioning
confidence: 99%
“…The utility of gene editing for GBM knowledge advancement has been solidly argued in human cell lines and organoid models [ 273 ], as well as animal models (for details on the genome engineering tools and models used, see [ 274 ]). It is continuously used for various purposes, such as screening for therapeutic targets or generation of cellular models and accurate animal disease models.…”
Section: Cell Therapy—a Novel Avenue To Pursue In Gbmmentioning
confidence: 99%
“…Besides its role in developing novel models for GBM as reviewed recently [ 104 ], CRISPR-Cas9 technology has offered novel insights into the unique and redundant roles of various genes in regulating proliferation, stemness, angiogenesis, and invasion of GBM cell lines, providing us promising therapeutic targets to treat or halt progression of this malignant disease. One of the major challenges of using this technology appeared obvious that viral Cas9 components were used in large number of GBM research, and this strategy could result in off-target editing and undesirable mutations.…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 99%